MECHANISM OF MANAGING PRODUCT SPECIALIZATION OF AGRICULTURAL ENTERPRISES - KALINICHENKO, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article reveals the organizational and economic principles of building a mechanism for managing the commodity specialization of agricultural enterprises. Factors affecting the reproduction of production resources as agricultural production factors are defined. It has been established that they have both a general economic character and are manifested at the level of subjects of agricultural management, are subjective or objective. The factors that determine the need for systemic legal influence on the management of commodity specialization of agricultural enterprises have been determined. The elements of the architecture of the organizational and economic mechanism of managing commodity specialization of agricultural enterprises have been developed and substantiated. The conceptual basis of the commodity specialization management mechanism assumes the definition of principles, goals, and tasks, as well as a set of tools for the agricultural specialization management mechanism, which is aimed at achieving sustainable functioning and development of enterprises. The specified concept takes into account the trends in the formation of economic potential, the internal infrastructure of the enterprise, the leading architectural solutions, and standards, the management model and requirements for management processes, and also defines the principles of transition from the existing state of the enterprise to the target one. It has been proven that this mechanism allows the implementation of adaptive strategies for the development of industrial and commercial activity due to the careful consideration of the effects of external and internal environmental factors when mobilizing the components of production and economic potential, as well as determining the configuration of product specialization management systems in enterprise management.
Keywords: specialization; management mechanism; branches of agriculture; agrarian enterprises; management factors and tools